Strategies towards Chemoselective Suzuki–Miyaura Cross-Coupling - Fyfe, James W. B.; Watson, Allan J. B. (Synlett, 2015)
Chemoselective Suzuki–Miyaura cross-coupling has emerged as a powerful method for the rapid preparation of sp2- and sp3-hybridized carbon frameworks based on control of the oxidative addition or transmetalation events. The field of chemoselective transmetalation has recently seen considerable development with several different strategies emerging including protected boronic acids, neighboring-group activation, and chemoselective speciation. Herein, these state-of-the-art approaches towards chemoselective Suzuki–Miyaura cross-coupling are highlighted.1 Chemoselective Suzuki–Miyaura Cross-Coupling via Control of Oxidative Addition2 Chemoselective Suzuki–Miyaura Cross-Coupling via Control of Transmetalation3 Development and Use of BMIDA Reagents4 Development and Use of BDAN Reagents5 Use of Vicinal and Geminal Diboron Species in Chemoselective Cross-Coupling6 Controlling Boron Solution Speciation7 Summary
Keywords: boron; catalysis; chemoselectivity; cross-coupling; palladium